Comparison of Age, Gender, and Bacteria Isolated with Antibiotics Resistance Patterns on Urine Cultures - Amir, Mumtaz; Malik, Ahmed Hassaan; Saleem, Muhammad Rehan (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare age, gender, and bacteria isolated from urine cultures with antibiotic resistance patterns.Study Design: Cross-sectional study.Place and Duration of Study: Surgery and Pathology Department Combined Military Hospital, Bannu Pakistan, from Jan 2023 to Apr 2024.Methodology: Three hundred and eighty-six patients aged 1 to 80 years with urinary tract infection symptoms were included. Patients having recurrent urinary tract infections, immunocompromised patients already taking antibiotics, and those with multiple co-morbid conditions were excluded. Urine cultures were evaluated, and the sensitivity/resistance pattern was compared with gender, age, and bacteria isolated in positive cases.Results: Forty-six samples were culture positive (11.9%). Escherichia coli was the most frequently isolated organism, obtained from 32 samples (69.6%), while Pseudomonas aeruginosa was isolated from 8 samples (17.4%), Klebsiella pneumoniae from 4(8.7%), Enterobacter from 1(2.2%) and Serratia liquefaciens from 1(2.2%) sample.  Resistance to Ampicillin was found in 30 samples (88.2%), Amoxicillin/Clavulanic acid 24(85.7%), Ciprofloxacin 23(74.2%), Ceftriaxone 18(69.2%), Levofloxacin 10(66.7%), Co-trimoxazole 21 samples (65.6%), Cefepime 9(36%), Gentamicin 7(33.3%), Meropenem 10(27%), Piperacillin/Tazobactum 3(14.3%), Fosfomycin 4(13.8%), Amikacin 4(10.5%), and Nitrofurantoin 3 samples (7.5%) respectively. No statistically significant difference was found for gender, age, or type of bacteria with antibiotic sensitivity/resistance profiles (p>0.05).Conclusion: Urinary tract bacteria resist most prescribed antibiotics, including Ampicillin, Amoxicillin/Clavulanic acid, Ciprofloxacin, Levofloxacin, Ceftriaxone, and Co-trimoxazole.